Sterilization effects of UV laser irradiation on Bacillus atrophaeus spore viability, structure, and proteins. Issue 24 (23rd November 2021) - Nguyen, My-Chi Thi; Nguyen, Huu-Quang; Jang, Hanbyeol; Noh, Sojung; Lee, Seong-Yeon; Jang, Kyoung-Soon; Lee, Jaebeom; Sohn, Youngku; Yee, Kiju; Jung, Heesoo; Kim, Jeongkwon
Abstract : A UV-C laser is capable of sterilizing Bacillus atrophaeus spores. Abstract : Bacillus spores are highly resistant to toxic chemicals and extreme environments. Because some Bacillus species threaten public health, spore inactivation techniques have been intensively investigated. We exposed Bacillus atrophaeus spores to a 266 nm Nd:YVO4 laser at a laser power of 1 W and various numbers of scans. As a result, the UV laser reduced the viability of Bacillus atrophaeus spores. Although the outer coat of spores remained intact after UV laser irradiation of 720 scans, damage inside the spores was observed. Spore proteins were identified by matrix-assisted laser desorption/ionization Fourier transform ion cyclotron resonance mass spectrometry during the course of UV laser irradiation. Photochemical and photothermal processes are believed to be involved in the UV laser sterilization of Bacillus spores. Our findings suggest that a UV laser is capable of sterilizing Bacillus atrophaeus spores.